(untitled) (Journal of Hama University, 2024)
Abstract The objective of the current research is identify the effectiveness of the Merrill and Tennyson model in developing some scientific concepts at the fourth grade students in science, the research adopted the semi- experimental approach, the research tools consisted of lesson plans according to the Merrill and Tennyson model, and scientific concepts test, the research sample consisted of (80) male and female students, it was divided into an experimental group consisting of (40) ) male and female students learned according to the Merrill and Tennyson model and a control group consisting of (40) ) male and female students learned according to the usual method, from Tawfiq Shishakli school, the search results indicated the following: • There are statistically significant differences between the mean scores of the experimental group and the control group in the post application of the scientific concepts test in favor of the experimental group. • There are statistically significant differences between the mean scores of the experimental group in the tribal and post application of the scientific concepts test in favor of the post application. • The research presented a set of proposals, including holding continuous training courses for teachers in modern teaching methods, including the Merrill and Tennyson model. Keywords: Merrill and Tennyson model, scientific concepts, science.